Parametarhizium (Clavicipitaceae) gen. nov. With Two New Species as a Potential Biocontrol Agent Isolated From Forest Litters in Northeast China - Gao, Siyu; Meng, Wei; Zhang, Lixiang; Yue, Qun; Zheng, Xu; Xu, Lijian (Frontiers in Microbiology, 2021)
A novel genus Parametarhizium with two new entomopathogenic species, P. changbaiense and P. hingganense was erected based on their morphological characteristics and a multigene phylogenetic analysis which were isolated from the forest litters collected in Northeast China. To infer their phylogenetic relationships a six-gene dataset consisting of DNA fragments of [Nuclear small subunit rDNA (SSU) + LSU + TUB + TEF + RPB1 + RPB2] were used for phylogenetic analysis, including 105 related fungi. The new genus Parametarhizium formed a monophyletic clade basal to Metarhizium and its related genera (formerly Metarhizium sensu lato). Parametarhizium can be morphologically distinguished from related genera by the combination of the following characters: formation of white to yellow colonies on different media, Candelabrum-like arrangement of cylindrical or obpyriform phialides and small subglobose to ellipsoidal conidia. Both of P. hingganense and P. changbaiense exhibited anti-insect activities against three farmland pests Monolepta hieroglyphica, Callosobruchus chinensis, and Rhopalosiphum maidis. This is the first report of entomopathogenic fungi exhibiting the anti-insect activity against Mo. hieroglyphica.